Cyclic voltammetry readout circuitry for DNA biosensor application - I. H. Hamzah; A. A. Malik; A. F. A. Rahim; Z. H. C. Soh (Institute of Advanced Engineering and Science, 2021)
Cyclic voltammetry electrochemical biosensors reported a wide usage and applications for its fast response, able to be miniaturized and its sensitivity. However, the bulky, expensive and laboratory-based readout circuitry made it impossible to be used in the field-based environment. A miniaturized and portable readout circuitry for the DNA detection using hybridization technique had been design and developed in this work. It embedded with fabricated FR4 based sensor and produced respective current when the applied voltage was within the range of 0 to 0.5 V. The readout circuitry had been verified with five analysis environments. Bare Au with distilled water (dH2O), bare Au with ferricyanide reagent solution, DNA immobilization, DNA non-hybridization and DNA hybridization. All the results performed produced peak cathodic current when the applied input voltage is within 0.5 V to 3 V and hence proved that the miniaturized and portable readout circuitry is suitable to be implemented for cyclic voltammetry electrochemical biosensor.